2016
DOI: 10.1038/ncomms10429
|View full text |Cite
|
Sign up to set email alerts
|

Graphene–ferroelectric metadevices for nonvolatile memory and reconfigurable logic-gate operations

Abstract: Memory metamaterials are artificial media that sustain transformed electromagnetic properties without persistent external stimuli. Previous memory metamaterials were realized with phase-change materials, such as vanadium dioxide or chalcogenide glasses, which exhibit memory behaviour with respect to electrically/optically induced thermal stimuli. However, they require a thermally isolated environment for longer retention or strong optical pump for phase-change. Here we demonstrate electrically programmable non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…Recently, Kim et al demonstrated electrically programmable nonvolatile memory and reconfigurable logic‐gate devices using the hybridization of graphene, a ferroelectric, and meta‐molecules . These metadevices operate at room temperature with superior nonvolatility and very flexible logic function.…”
Section: Graphene‐ferroelectric Metadevicesmentioning
confidence: 99%
“…Recently, Kim et al demonstrated electrically programmable nonvolatile memory and reconfigurable logic‐gate devices using the hybridization of graphene, a ferroelectric, and meta‐molecules . These metadevices operate at room temperature with superior nonvolatility and very flexible logic function.…”
Section: Graphene‐ferroelectric Metadevicesmentioning
confidence: 99%
“…The effects eventually leads to the size-induced phase transition to a paraelectric phase with the film thickness decrease below the critical thickness . At that the critical thickness depends on the gap and/or dead layer thickness in a self-consistent way, and usually does not exceed (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) only, it appeared proportional to both of these values. Actually, the full step width w, defined as the distance between its maximal positive and negative displacement (shown by a horizontal arrow in Fig.2), can be estimated from the expression:…”
Section: Surfacementioning
confidence: 99%
“…The consideration of the first of these three effects, performed in this work, are promising for advanced applications of graphene-on-ferroelectric with domain structure in GFETs and related memory elements, various logic devices, as well as for design of high efficient hybrid electrical modulators, rectifiers and transducers of voltage-to-current type [7][8][9][10][11][12][13][14][15][16]21].…”
Section: Graphene Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…Kurchak et al [22,23] revealed that adsorbed charges dynamics leads to the hysteresis effect on conductivity in the graphene channel on an organic ferroelectric substrate. Kim et al [24] propose graphene on ferroelectric for nonvolatile memory and reconfigurable logic-gate operations.…”
Section: Introductionmentioning
confidence: 99%